High maternal pre-pregnancy BMI is associated with increased offspring peer-relationship problems at 5 years - Dow, Courtney; Lorthe, Elsa; Galera, Cédric; Tafflet, Muriel; Marchand-Martin, Laetitia; Ancel, Pierre-Yves; Charles, Marie-Aline; Heude, Barbara (Frontiers in Child and Adolescent Psychiatry, 2022)
Background Peer relationships are an important aspect of child development that are often overlooked. Maternal pre-pregnancy body mass index (BMI) may influence peer relationships through intrauterine mechanisms affecting fetal neurodevelopment or through postnatal mechanisms including social discrimination of the obese mother/child. This study aimed to determine the relationship between maternal pre-pregnancy BMI and child peer-relationship problems around 5 years old, including preterm and term-born children. Methods and findings Maternal BMI and offspring peer-relationship problems were assessed in participants of three French birth cohorts: EDEN (n = 1,184 children born at term), ELFE (n = 10,889 children born ≥33 weeks of gestation) and EPIPAGE-2 (n = 2,646 children born 23–34 weeks of gestation). Reported or measured pre-pregnancy weight (kg) and height (m) were collected from mothers and used to calculate BMI (kg/m2). Offspring peer-relationship problems were assessed using the Strengths and Difficulties Questionnaire at 5.5 years. Logistic regression was used to estimate odds ratios (OR) of a high peer-relationship problem score (≥3) in EDEN and ELFE, and generalized estimated equations were used in EPIPAGE-2 to account for the large number of multiple births. Paternal BMI was used as a negative control in sensitivity analyses. Maternal pre-pregnancy obesity was associated with increased odds of a high peer-relationship problem score in all three cohorts, independent of confounding factors [adjusted OR 2.27 (1.32, 3.88); 1.52 (1.29, 1.78); 1.44 (1.04, 1.99); for EDEN, ELFE and EPIPAGE-2, respectively]. Additional analysis based on negative controls (i.e., adjusting for paternal BMI) showed the same pattern of associations. Conclusion High maternal pre-pregnancy BMI is associated with greater likelihood of a high peer-relationship trouble score in offspring around 5 years of age in both children born preterm and at term.